2016
DOI: 10.1589/jpts.28.286
|View full text |Cite
|
Sign up to set email alerts
|

Comparative gait analysis between children with autism and age-matched controls: analysis with temporal-spatial and foot pressure variables

Abstract: [Purpose] The purpose of this study was to investigate the gait pattern of children with autism by using a gait analysis system. [Subjects] Thirty children were selected for this study: 15 with autism (age, 11.2 ± 2.8 years; weight, 48.1 ± 14.1 kg; height, 1.51 ± 0.11 m) and 15 healthy age-matched controls (age, 11.0 ± 2.9 years; weight, 43.6 ± 10 kg; height, 1.51 ± 0.011 m). [Methods] All participants walked three times on the GAITRite® system while their plantar pressure was being recorded. [Results] The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 22 publications
1
29
0
Order By: Relevance
“…These children demonstrated increased variability in the time taken to prepare simple point-point movements relative to typically developing controls leading authors to hypothesize that these findings could support differences in visual processing and visual-motor integration [35]. The use of gait analysis systems that utilize foot pressure variables have shown that children with ASD have wider step width, reduced step rate (cadence), and increased variability in step length [36, 37]. These findings have led researchers to conclude that disruptions in cerebellar and fronto-striatal basal ganglia function are the reason for abnormal movement in ASD [37].…”
Section: Discussionmentioning
confidence: 99%
“…These children demonstrated increased variability in the time taken to prepare simple point-point movements relative to typically developing controls leading authors to hypothesize that these findings could support differences in visual processing and visual-motor integration [35]. The use of gait analysis systems that utilize foot pressure variables have shown that children with ASD have wider step width, reduced step rate (cadence), and increased variability in step length [36, 37]. These findings have led researchers to conclude that disruptions in cerebellar and fronto-striatal basal ganglia function are the reason for abnormal movement in ASD [37].…”
Section: Discussionmentioning
confidence: 99%
“…Sairanen M et al 8 ) reported that ASD is characterized by structural defects that include a reduction in forebrain volume and disruption of the neural network between the limbic system and other cerebral cortex regions. In addition, recent study demonstrated that ASD children presented an abnormal gait compared with that of age-matched controls, they showed a reduction in cadence, gait velocity, step length, and an increase in step width 9 ) . Interestingly, therapeutic physical exercise in patients with ASD increases hippocampal volume and promotes the robust growth of newly proliferated and/or differentiated cells by increasing brain-derived neurotrophic factor (BDNF) in the cerebral cortex 10 ) .…”
Section: Therapeutic Physical Exercise In Patients With Autistic Fragmentioning
confidence: 99%
“…In 2015, Kindregan et al (2015) , conducted a review on walking biomechanics in children with ASD and concluded to a more unstable gait in patients affected by ASD. Since the publication of the review by Kindregan et al, other studies analyzed gait biomechanics in children with ASD ( Lim et al, 2016 ; Dufek et al, 2017 ; Eggleston et al, 2017 , 2020 ; Hasan et al, 2017 ; Biffi et al, 2018 ; Manicolo et al, 2019 ). The results from these works and from the studies in the review by Kindregan et al are summarized in Figure 1 .…”
Section: Motor Deficit In Asdmentioning
confidence: 99%
“… Gait biomechanics data found in children with ASD, in comparison to control groups, matched for age and gender; (1) Manicolo et al (2019) ; (2) Biffi et al (2018) ; (3) Hasan et al (2017) ; (4) Eggleston et al (2017) ; (5) Dufek et al (2017) ; (6) Lim et al (2016) —CV Coefficient of variation; (7) Eggleston et al (2020) (8) Kindregan et al (2015) —review of 11 studies assessing gait biomechanics in children with ASD. …”
Section: Motor Deficit In Asdmentioning
confidence: 99%